Responding to Social Unrest Through Punjari Kumoro Traditional Ritual In Banyuwangi, East Java, Indonesia - Mochamad Maskur (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2023)
This research aims to raise public awareness of the importance of social life by prioritizing the noble values contained in the principles of local culture. The packaging of this work is more focused on creating an atmosphere by combining several types of music from Banyuwangi. The music mentioned are angklung paglak, music on Gandrung arts, and Kunthulan which are worked on optimally so that they can strengthen the desired atmosphere and create new nuances on the musical side. Kumarajana's musical work also presents elements of the values embodied in the Punjari Kumoro art. The content and meaning of the Punjari Kumoro Ritual itself are implied by the values of life in a social context. These values are religious values as a means to pray and ask God to give guidance. The value of togetherness, in this case the people of Aliyan village mingle and unite their hearts and minds for the same goal. Other values include the value of mutual respect as an effort by the community to respect nature as a source of life for them.